2005
DOI: 10.1038/sj.onc.1209002
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-triggered Lipoxin A4 inhibition of VEGF-induced endothelial cell migration involves actin polymerization and focal adhesion assembly

Abstract: Angiogenesis, the growth of new capillaries from preexisting ones, occurs through dynamic functions of the endothelial cells (EC), including migration, which is essential to achieve an organized formation of the vessel sprout. We demonstrated previously that an aspirintriggered lipoxin analog, 15-epi-16-(para-fluoro)-phenoxylipoxin A 4 (ATL-1), inhibits vascular endothelial growth factor (VEGF)-induced EC migration. In the present study, we investigated the effects of ATL-1 in the actin cytoskeleton reorganiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 41 publications
6
54
1
Order By: Relevance
“…It has been shown that ATL-1 inhibits the VEGF-induced formation of actin stress fibers, but ATL-1 alone does not have the same effect (30). On the contrary, in our experimental conditions, native LXA 4 causes a profound change in actin rearrangement.…”
Section: Lxa 4 Stimulates Actin Rearrangement and Inhibits Vegf-and Lcontrasting
confidence: 42%
See 1 more Smart Citation
“…It has been shown that ATL-1 inhibits the VEGF-induced formation of actin stress fibers, but ATL-1 alone does not have the same effect (30). On the contrary, in our experimental conditions, native LXA 4 causes a profound change in actin rearrangement.…”
Section: Lxa 4 Stimulates Actin Rearrangement and Inhibits Vegf-and Lcontrasting
confidence: 42%
“…Work by Fierro and colleagues has shown the stable synthetic analog of ATL, 15-epi-16-(para-fluoro)-phenoxy-LXA 4 (ATL-1), inhibits VEGF-and LTD 4 -stimulated angiogenesis in vitro and in vivo (29 -31). Additionally, ATL-1 has been shown to regulate the proteolytic activity necessary to digest basement membrane (30) and to modulate endothelial cell migration (31), key events in the angiogenic process (32).…”
mentioning
confidence: 99%
“…41 Also, VEGF activates the p38 MAPK pathway that is required for mitogenic activity in ECs and has been EMAP II interferes with VEGF signaling N Awasthi et al implicated in cell migration. 42,43 In our study, we observed that EMAP II preincubation inhibited VEGF-induced activation of elements of all these downstream signaling pathways, namely Raf, Erk1/2, Akt and p38. This inhibition of phosphorylation of VEGF-induced cytoplasmic signaling proteins likely reflects a functional interference with the VEGF to VEGFR interaction, and represents a mechanism for the known effects of EMAP II on survival, proliferation, differentiation and migration of ECs.…”
Section: Discussionmentioning
confidence: 70%
“…This finding correlates with our observation that EMAP II blocks VEGF-induced activation of p38 MAPK, which has been implicated in EC migration. 42,43 In summary, our study demonstrated that EMAP II interacts with VEGF receptors, which inhibits VEGF receptor activation and causes inhibition of VEGF-induced activation of downstream signaling proteins. We also showed that EMAP II inhibits VEGF-induced ECs proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, both VEGF and mechanical signals are known to regulate common elements such as polymerisation of actin and FAK and PI3K activation (1) (45) (11).…”
Section: Introductionmentioning
confidence: 99%